ACACIA GLULAM WOOD EXTERIOR BEAM-COLUMN CONNECTION WITH ANGLES AND STEEL ROD SYSTEM - Djoni Simanta; Bambang Suryoatmono; Johannes Adhijoso Tjondro (MEKANIKA, 2016)
Two models of acacia glulam wood exterior beam-column connections with angles and steel rod system under monotonic static loads were tested and analyzed. The variation of the specimen was number of rod and thickness of angles attached at the beam. The behavior of each model under static loading, maximum displacement, maximum moment, rotational stiffness and ductility were observed. M9B1 type connections have more flexible than M9B2 type connections. The behavior of connection was depened on number of bearing steel rods at the beam, wood quality and thickness of the angles.